Kewajiban Laki-Laki dalam Hak Nafkah Kerabat Perempuan (Studi Komparatif Mazhab Syafii dan Hambali): Men’s Obligations in Maintenance Rights of Female Relatives (Shafi‘I and Hambali's School Comparative Study) - Andi Alif Anugrah Hamzah; Said Syaripudin; Nuraeni Abdullah; M. Akil (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the obligations of men in fulfilling the maintenance rights of female relatives from the perspectives of the Shafi‘i and Hambali schools, which aims to identify the female relatives who are entitled to receive maintenance and the priority order of men who are obliged to provide the maintenance to those female relatives. The research is motivated by contemporary social conditions in which many households rely economically on women, while Islamic law places that responsibility on men. Using a library research method with a comparative normative descriptive approach, this study analyzes classical fiqh texts representing both schools, supported by secondary sources from academic literature and relevant journals. The findings show that both the Shafi‘i and Hambali schools agree that ascendants (uṣūl) and descendants (furū‘) are entitled to financial maintenance. However, the Hambali school adopts a broader scope by including all heirs (ahl al-mīrāth). In determining priorities, the Shafi‘i school prioritizes the closeness of lineage, while the Hambali school uses the order of inheritance rights as the basis. This research is expected to contribute to a more systematic understanding of the responsibility for maintenance in Islamic law and serve as a reference for future research on Islamic family law.